2015
DOI: 10.1177/1356336x14568126
|View full text |Cite
|
Sign up to set email alerts
|

Insideness and outsideness

Abstract: The purpose of this study is to provide an authentic and legitimate voice to the physical education (PE) specialist teacher in the primary school and to give an insight into professional knowledge. An autoethnographic approach has been used to invite readers to enter my world of the primary PE specialist teacher and observe and respond to its social and cultural practices. Teacher professionalism as a cultural practice is defined, perceived and enacted in different ways over the three years I spent as a primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Limited contact with students: Classroom teachers vs. specialist teachers Subject specialist teachers in each country have long and complicated histories, but their profession has emerged to enhance the teacher professionalism frequently mentioned in elementary education (Barney & Deutsch, 2012;Brooks & Thompson, 2015). Although specialist teachers were introduced to provide quality subject classes to students, the research participants reported that specialist teachers play a minor role in the safety of students' PE classes.…”
Section: Breaches Of Safety Codes Between Teacher and Administrator: mentioning
confidence: 99%
“…Limited contact with students: Classroom teachers vs. specialist teachers Subject specialist teachers in each country have long and complicated histories, but their profession has emerged to enhance the teacher professionalism frequently mentioned in elementary education (Barney & Deutsch, 2012;Brooks & Thompson, 2015). Although specialist teachers were introduced to provide quality subject classes to students, the research participants reported that specialist teachers play a minor role in the safety of students' PE classes.…”
Section: Breaches Of Safety Codes Between Teacher and Administrator: mentioning
confidence: 99%